Analisis Psikologi Tokoh Utama Dalam Novel “Siluetcinta Sang Kelana” Karya Robertus Adi Sarjono Owon (Kajian Psikologi Sastra) - Subandi Subandi; Rimasi Rimasi; Robertus Adi Sarjono (LPPM Politeknik Pratama, 2023)
The goal of this study was to understand the psychology of the id, ego, and super ego that the protagonist of Robertus Adi Sarjono Owon's novel Siluet Cinta Sang Kelana experienced. Such a study is both qualitative and descriptive. The material used in this study serves as evidence for the psychological states of the characters in Robertus Adi Sarjono Owon's novel Siluet Cinta Sang Kelana by making every word or sentence the subject of investigation. Reading, recording, and data analysis techniques were all employed in the process of gathering study data. According to the study's findings, Robertus Adi Sarjono Owon's